Analysis of Work Station Capacity Planning Efficiency in A Steel Fabrication Project Using the Theory of Constraints Method (TOC) - Rachmah, Salsa Auliya; Suryadi, Akmal (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2025)
PT XYZ is a company engaged in steel fabrication, and there are several issues related to the production system of the PT Metso project that are known to be the source of bottlenecks at certain workstations, causing material flow on the production line to be impeded.  This research will discuss the calculation of standard time and identify bottlenecks at several workstations. The application of the theory of constraints that can help identify and control the sources of constraints with several objectives such as maximizing throughput and creating detailed calculations of time buffers and Drum Buffer Rope maps to address issues. Then an analysis was conducted using a fishbone diagram and the Five-M Analysis method to determine the causes that occurred. Based on the calculations that have been made for the company's capacity and capability, a rescheduling of the Spray Bar production process has been carried out with an additional working time of 19 hours divided into 2.5 hours per working day. It is known that the bottleneck workstation is located at the Fit-up/Setting workstation with a percentage of 133%. To reduce this bottleneck, the company provides buffer time or time that serves as a cushion with the aim of protecting the production rate (throughput) Before the bottleneck workstation, it took 19.5 hours, and after the bottleneck workstation, it took 2.2 hours.